2022
DOI: 10.1097/meg.0000000000002419
|View full text |Cite
|
Sign up to set email alerts
|

Objectively confirmed gastroesophageal reflux disease and risk of atrial fibrillation: a population-based cohort study in Sweden

Abstract: Objective This study aimed to determine the risk of atrial fibrillation in patients with objectively confirmed GERD. Methods This was a nationwide population-based cohort study between 2005 and 2018, including the majority (n = 8 421 115) of all Swedish adult residents (≥18 years). Within this cohort, the exposed group were all individuals with a diagnosis of esophagitis or Barrett’s esophagus, and the unexposed group was made up of five times as many individuals without any GERD, matched by age, sex, and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…However, since AF was rare among young participants, the estimates obtained in these analyses were imprecise. These findings concur with a recent register-based population study that investigated whether objectively determined esophagitis or Barrett's esophagus increases the risk of AF [12]. The investigators found an increased risk of AF among patients younger than 60 years of age who had a HR of 1.55 (95% CI, 1.27 to 1.88) within the first year of diagnosis but the excess risk decreased afterward (HR: 1.14; 95% CI, 1.06 to 1.22).…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…However, since AF was rare among young participants, the estimates obtained in these analyses were imprecise. These findings concur with a recent register-based population study that investigated whether objectively determined esophagitis or Barrett's esophagus increases the risk of AF [12]. The investigators found an increased risk of AF among patients younger than 60 years of age who had a HR of 1.55 (95% CI, 1.27 to 1.88) within the first year of diagnosis but the excess risk decreased afterward (HR: 1.14; 95% CI, 1.06 to 1.22).…”
Section: Plos Onesupporting
confidence: 91%
“…If an association is found between GERD and AF, it could give us a novel opportunity for prevention of AF in selected patients. Previous studies have shown divergent results and had limited possibilities to adjust for potential confounders [12][13][14][15][16]. We therefore investigated the association between self-reported GERD symptoms and the risk of AF in a large population based study with validated AF diagnoses during the follow up and extensive data on potential confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Other mechanisms suggested for the development of LVZs include hormonal factors 26 and the presence of excessive epicardial fat, which can lead to local inflammation. 27 Numerous studies have shown the association between AF and GERD, 14 , 15 , 28 and the concept of “cardiogastric interaction” was delineated by Linz et al, 29 who highlighted the potentially involved mechanisms. These are suggested to encompass local and systemic inflammation, chemical or mechanical irritation, and irritation of the vagal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Such regurgitation can lead to chronic inflammation, characterized by the release of various proinflammatory mediators. 32 A study performed by Maret-Ouda et al 28 showed that inflammation in the esophagus, verified through gastroscopy, was independently associated with AF. Our study revealed an independent association between GERD and the presence of LVZs in the posteroinferior regions of the LA.…”
Section: Discussionmentioning
confidence: 99%
“…There is likely a link between GERD and AF due to their shared risk factors, including sleep apnea, obesity, and local inflammation that worsens with age (2). The prospective observational studies and retrospective database analysis suggest an association between GERD and AF (3)(4)(5)(6). A systematic review showed the summary-adjusted relative risk for GERD-induced AF was 1.06 (95% CI, 0.86-1.31) (7).…”
mentioning
confidence: 99%